Radical Intellectuals and the Subversion of Progressive Politics
304 p.
Keywords: Radical Intellectuals and the Subversion of Progressive Politics is a challenge to contemporary radical politics and political thought. This collection of essays critiques the dominant trends and figures on the left that have distorted the legacy of progressive politics, arguing that they have moved politics away from issues of class and economic power toward a preoccupation with culture and identity. The contributors discuss this new radicalism from the perspective of a more rational form of leftism capable of reviving interest in a more politically relevant form of politics.